2020
DOI: 10.1111/emre.12396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multidimensional Intellectual Capital and Organizational Learning Practices in Innovation Performance

Abstract: The purpose of this paper is to explore how managers transform human, renewal, and entrepreneurial capital through specific organizational learning practices into superior innovation performance. We draw implications for managing organizational learning and guiding companies on how to create innovation-based competitive advantages grounded in the human aspects of intellectual capital. The study is based on a survey of companies located in the transitional economy of Serbia. We found that human, renewal, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 164 publications
(376 reference statements)
4
53
0
2
Order By: Relevance
“…These findings are consistent with the existing literature that demonstrated the positive role of human capital in enhancing commercial banks' performance compared with intellectual capital development [29,30]. The results are in good agreement with several reported works displaying the evidence of a noteworthy link between structural capital and innovation performance [47,71,[114][115][116][117].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the existing literature that demonstrated the positive role of human capital in enhancing commercial banks' performance compared with intellectual capital development [29,30]. The results are in good agreement with several reported works displaying the evidence of a noteworthy link between structural capital and innovation performance [47,71,[114][115][116][117].…”
Section: Discussionsupporting
confidence: 92%
“…In past decades, several researchers highlighted the necessity to develop a modern perspective to achieve innovation performance in a firm [27,[44][45][46]. Driven by this idea, many frameworks have been developed that depend on research backgrounds and subjects without using any consistent design strategy [47,48].…”
Section: Theoretical Background and Hypothesis Development 21 Implications Of Intellectual Capital On Innovation Performancementioning
confidence: 99%
“…It combines the skill, innovativeness and ability of the employees to perform their duties so that it creates value, allowing the organisation to fulfil its objectives [41]. Relational capital helps managers to derive the knowledge from their environment that enables them to offer better services and products to their customers and understand their needs [84]. Hence, relational capital interacts with human capital to determine the impacts of the surrounding environment on the organisation, addressing all required issues for a successful business [48].…”
Section: Human Capital and Relational Capitalmentioning
confidence: 99%
“…In Systematic studies showed that some aspects of intellectual capital from a multifaceted viewpoint are consistent with the desired objectives of the financial markets (Asiaei et al 2020). Recently, there has been a growing demand to conduct empirical studies for gaining an in-depth knowledge about intellectual capital components due to their multidimensional traits (Cabrilo and Dahms 2020). However, appropriate hypotheses must be made and the effects of intellectual capital components on the innovation performance of an organization must be measured accurately to develop some comprehensive arguments regarding the proper management of various intellectual resources.…”
Section: Human Capitalmentioning
confidence: 99%
“…Several manufacturing firms are engaged themselves in intimate relations with the suppliers to use their skill, capability, and knowledge for developing novel and low-cost products at rapid space (Vătămănescu et al 2019). Thus, friendly relations with the suppliers can positively affect the innovation performance of a manufacturing organization (Cabrilo and Dahms 2020). Based on these factors, this study assumed that relational capital positively affects the innovation performance.…”
Section: Relational Capitalmentioning
confidence: 99%